Facility manager's portable handbook - Lewis, Bernard T. (McGraw-Hill portable engineering., 2000)
"This operations and maintenance problem-solver helps you keep your facility running at its peak. Filled with tables, charts, and checklists, the Facility Manager's Portable Handbook is ideal for success-minded maintenance managers and engineers, facility and operations managers, and others."--BOOK JACKET.